Measuring Corporate Social Performance in France: A Critical and Empirical Analysis of ARESE Data - Igalens, Jacques (Journal of business ethics, 2005)
This article studies the idea of Corporate Social Performance (CSP) from a critical perspective using empirical elements derived from analysis of year 2000 ARESE data. ARESE is the French first mover “social rating agency” providing quantified data about the Social Performance of French companies. The paper starts out by reviewing leading CSP models and discussing problems inherent to the measurement of this construct before going on to present and analyse ARESE data - whose suitability for existing models will be discussed.